2023
DOI: 10.1111/cas.15704
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate prediction of nasopharyngeal carcinoma patients based on MRI and gene expression using a deep neural network

Abstract: To achieve a better treatment regimen and follow‐up assessment design for intensity‐modulated radiotherapy (IMRT)‐treated nasopharyngeal carcinoma (NPC) patients, an accurate progression‐free survival (PFS) time prediction algorithm is needed. We propose developing a PFS prediction model of NPC patients after IMRT treatment using a deep learning method and comparing that with the traditional texture analysis method. One hundred and fifty‐one NPC patients were included in this retrospective study. T1‐weighted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The allocation of articles from each database and the refinement process to identify relevant studies are detailed in Table S2. After comprehensive analysis, 15 studies were included in our meta-analysis [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], with the exclusion rationale documented in Table S3 [8,10,34,.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…The allocation of articles from each database and the refinement process to identify relevant studies are detailed in Table S2. After comprehensive analysis, 15 studies were included in our meta-analysis [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], with the exclusion rationale documented in Table S3 [8,10,34,.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Moreover, the 4-mRNA signature was related to the immune response as well as cell proliferation [98]. Zhang et al used the deep network to predict the prognosis of NPC based on MRI and gene expression, and the AUC was 0.88 [99].…”
Section: Ai and Npc Prognosis Predictionmentioning
confidence: 99%
“…The study confirmed the great potential of DRN and its derived models for predicting survival in patients with rectal cancer. Zhang et al 28 used DRN to develop a prediction model for 1-year progression-free survival after intensity-modulated radiotherapy in patients with nasopharyngeal carcinoma and compared it with the conventional texture analysis. The final AUC of the DRN model based on MRI images was 0.85, and the AUC was improved to 0.88 after combining genetic data, both higher than that of texture analysis at 0.76.…”
Section: Cancer Prognostic Model Based On Deep Residual Networkmentioning
confidence: 99%